Techno-economic analysis of electricity generation from biogas using palm oil waste - Begum S.; Saad M.F.M. (2023)
In Malaysia, nearly 80 million tons of fresh fruit bunches are processed annually in 406 palm oil mills and are generating approximately 54 million tons of Palm Oil W11 Effluent (POME). This POME is known to generate biogas consisting of methane-a Green House Gas (GHG) identifiable to cause global warming. The amount of methane gas generated annually is equivalent to 19 million tons of carbon dioxide. To meet the regulatory requirement, more than 85% of the mills use solely the lagoon systems in waste water treatment, typically anaerobic first stage followed by facultative treatment. However, these two major palm oil wastes are a viable Renewable Energy (RE) source for production of electricity. In the present paper, an attempt has been made to study the technological parameters for hfferent capacity digester to produce electricity. The cost related data are collected from Serting Hilir Palm Oil Mill. Net present worth, internal rate of return and payback period were calculated. On the basis of the calculated values it has been found that the application of biogas plant for generation of electricity is economically viable in Malaysian perspective and this viability or economic attractiveness increase with the increase of plant size. The findings of this study should be useful to give some directions and guidelines for future planning and implementation of biogas plants in Malaysia. 2013 Asian Network for Scientific Information.